Longitudinal Association between Sarcopenia and Cognitive Impairment among Older Adults in Rural Malaysia - K. Ramoo (International Journal of Environmental Research and Public Health, 2022)
Sarcopenia is a condition that is highly prevalent among older adults. This condition is linked to numerous adverse health outcomes, including cognitive impairment that impairs healthy ageing. While sarcopenia and cognitive impairment may share a common pathway, limited longitudinal studies exist to show the relationship between these two conditions. Therefore, this study aimed to examine the longitudinal association between sarcopenia and cognitive impairment. This is a cohort study among older adults residing in Kuala Pilah District, Negeri Sembilan, Malaysia. There were 2404 respondents at the baseline and 1946 respondents at one-year follow-up. Cognitive impairment was determined using Mini-mental State Examination scores. Sarcopenia was identified using the Asian Working Group for Sarcopenia 2019 criteria, gait speed was measured using a 4-meter gait test, handgrip strength was assessed using Jamar handheld dynamometer, and appendicular skeletal muscle mass was measured using bioelectrical impedance analysis. Generalized estimating equation (GEE) was used to determine the longitudinal association between sarcopenia and cognitive impairment, presented as relative risk (RR) and its 95% confidence interval. The prevalence of sarcopenia was 5.0% (95% CI 4.00–5.90), and severe sarcopenia was 3.60% (95% CI 2.84–4.31). Upon adjusting for covariates, older adults with sarcopenia have an 80 per cent increased risk of cognitive impairment compared to those without (RR 1.80; 95% CI 1.18–2.75). Similarly, severe sarcopenia was found to significantly increase the risk of cognitive impairment by 101 per cent in the adjusted model (RR 2.01; 95% CI 1.24–3.27). Our study showed that sarcopenia, severe sarcopenia, low physical activity, depressive symptoms, hearing impairment and chronic pain were associated with a higher risk of cognitive impairment among community-dwelling older adults. Therefore, early intervention to prevent sarcopenia, depressive symptoms, hearing impairment, chronic pain, and higher physical activity among older adults is recommended.